1992
DOI: 10.1259/0007-1285-65-780-1075
|View full text |Cite
|
Sign up to set email alerts
|

99TcmTechnegas and krypton-81m ventilation scintigraphy: a comparison in known respiratory disease

Abstract: Krypton-81m gas, by virtue of its imaging characteristics, is often considered the "gold standard" for ventilation scintigraphy but its use is restricted by its high cost and limited availability. The new radiopharmaceutical 99Tcm-Technegas, a suspension of ultrafine technetium-99m labelled carbon particles, produces high-quality images of ventilation and has the advantage of continuous availability. As part of our evaluation of Technegas the two were compared in 40 patients with a variety of established respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…However, pharmacologically induced bronchoconstriction increases the deposition in central airways, resulting in different distributions of Technegas and 81m Kr (64). Technegas deposition in central airways in patients with chronic obstructive pulmonary disease has also been reported in some clinical studies (21,38). Hinz et al (35) found a good correlation between SPECT measurements of regional ventilation obtained with Technegas and 81m Kr in an animal model of acute lung injury.…”
Section: Active Regulation Of Lung Blood Flowmentioning
confidence: 94%
“…However, pharmacologically induced bronchoconstriction increases the deposition in central airways, resulting in different distributions of Technegas and 81m Kr (64). Technegas deposition in central airways in patients with chronic obstructive pulmonary disease has also been reported in some clinical studies (21,38). Hinz et al (35) found a good correlation between SPECT measurements of regional ventilation obtained with Technegas and 81m Kr in an animal model of acute lung injury.…”
Section: Active Regulation Of Lung Blood Flowmentioning
confidence: 94%
“…[29][30][31][32][33] This reflects the fact that Technegas particles are so small that the aerosol closely follows the gas flow down to the alveoli, where they are deposited by diffusion. 31,34 In comparison with liquid radio-aerosols, Technegas has significantly fewer problems of central airway deposition and peripheral "hotspot" formation in patients with obstructive lung disease. Recently, a group of patients routinely admitted for V/Q SPECT and a group of patients with known COPD were studied head to head with [ 99m Tc]-DTPA and Technegas.…”
Section: Comparison Of Ventilation Agentsmentioning
confidence: 99%
“…The small particle size implies that they are distributed in the lungs almost like a gas and are deposited in alveoli by diffusion (James et al, 1992). Technegas provides images which are equivalent to those with 81mKr.…”
Section: Ventilationmentioning
confidence: 99%